2021
DOI: 10.3390/genes12050741
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of a Health Threat: Illness Representations, Coping, and Psychological Distress among BRCA1/2 Mutation Carriers

Abstract: Little is known about how women with a BRCA1/2 mutation develop an individual understanding of their breast and ovarian cancer risk and how this affects their psychological distress. In this study, we investigated associations between illness representations, coping strategies and psychological distress. N = 101 BRCA1/2 mutation carriers answered self-report questionnaires on illness representations, coping strategies, cancer worry and depressive symptoms. Women without cancer were compared to women with a pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These findings demonstrate that the detection of a mutation can cause cancer fear and lead to psychological distress. However, it should be emphasized that study results dealing with the psychological impact of genetic testing are heterogenous 4 , 6 , and that other research showed no significant decrease in psychological well-being due to the detection of a pathogenic mutation, especially considering the intermediate- and long-term outcome after test disclosure.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings demonstrate that the detection of a mutation can cause cancer fear and lead to psychological distress. However, it should be emphasized that study results dealing with the psychological impact of genetic testing are heterogenous 4 , 6 , and that other research showed no significant decrease in psychological well-being due to the detection of a pathogenic mutation, especially considering the intermediate- and long-term outcome after test disclosure.…”
Section: Discussionmentioning
confidence: 91%
“…In addition to medical consequences, the detection of a mutation in a cancer predisposing gene also has psychosocial impact. It can be perceived as a psychological burden by some mutation carriers 4 6 , not only resulting from uncertainties and fears concerning the own future prospects, but also from the responsibility to inform relatives about their individual risk to carry the same mutation and its associated cancer risks. In order to advise family members, a mutation carrier has to understand the test result and its clinical consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen studies measured cancer worry utilizing different versions of the CWS [ 37 , 38 , 44 , 48 , 56 , 57 , 62 , 73 , 75 , 76 , 78 , 79 , 81 ]. There was high heterogeneity in the versions used, with one study using a single-item version [ 76 ], two studies using a three-item version [ 37 , 56 ], five studies using a four-item version [ 38 , 44 , 73 , 75 , 79 ], two studies using a five-item version [ 62 , 78 ], and two studies using a revised six-item version [ 48 , 81 ]. One study did not specify which version was used [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies identified no difference in cancer worry in carriers when compared to non-carriers from high-risk families [ 48 , 73 , 78 ]. In contrast, eight studies identified increased cancer worry, each with unique comparators [ 37 , 38 , 44 , 62 , 75 , 76 , 79 , 81 ]. Three studies compared carriers with non-carriers from high-risk families and found higher cancer worry in those with pathogenic variants for up to one year after genetic test result disclosure [ 44 , 79 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ethical approval was obtained from Charité—Universitätsmedizin Berlin (EA1/222/15). The study is described in more detail elsewhere [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%